Vėlyvųjų viduramžių Europa ir Lietuvos Didžiosios Kunigaikštystės visuomenės ir kultūros raida XIV-XVI amžiuje - Petrauskas, Rimvydas (Lietuvos istorijos studijos, 2009)
The article aims to discuss the history of the Grand Duchy of Lithuania (GDL) in XIV-XVI cc. in the light of the spreading of late medieval civilization. The first part presents methodological assumptions of such an approach. The second part describes the most important social, political, and cultural trends in the history of late middle ages in Europe. The third part analyzes individual aspects of GDL's involvement into the European medieval civilization. In XIII-XIV cc. Lithuanian society and statehood were emerging and developing under the influence of European Christendom. The very emergence of statelike formation in the middle of the XIII century demonstrated the decisive impact of European structures and notions on the historical genesis of Lithuania. Therefore, the changing relationship between late medieval Europe and GDL is an important historical issue. The falling back of the core territories of the Lithuanian state to paganism and their belated Catholic Christianization, incorporation of the Christian Orthodox lands, and the eastward territorial expansion of Lithuania shaped the distinct features of GDL's development. Nevertheless, throughout the whole period in question, one can observe gradual spreading of elements of the late medieval European civilization in GDL - concepts of a monarch and the ruling house, idea of Christian estates and knightly ideology, church foundations, patronage and the cults of saints, the early noble parliamentarianism, the urban and rural self-government as well as self-government of ethnic and confessional groups, large landownership and colonization, political and literary writings, codification of the law and historical thinking. This process of socio-cultural adaptation has resulted in deep change in Lithuanian society and worldviews of its different social groups.